Failures of the "Invisible Hand". Issue 1 (2nd January 2016) - Amir-ud-Din, Rafi; Zaman, Asad
Abstract : Despite many failures of the invisible hand both empirically and theoretically, it continues to be vigorously asserted and widely believed. We document the failures and explain why it continues to be asserted despite these failures.